Regime de tributação dos lucros auferidos por controladas no exterior e os tratados para evitar a bitributação - Santos, Edigar Bernardo dos (2021)
In tax matters, the Brazilian rules that deal with the incorporation of treaties, specifically Article 98 of the National Tax Code, provide that international treaties preempt domestic legislation. However, the national system for the taxation of profits earned by foreign subsidiaries establishes that profits be taxed on the 31st of December of the calendar year in which they were earned, even though the profit may have been held back abroad by the foreign subsidiary. This contradicts Paragraph 1 of Article 7 of the double taxation avoidance treaties (Treaties), which confers jurisdiction to tax only to the country where the entity that generated the profit is located and, therefore, prevents Brazil from taxing that profit. In order to collect funds at any cost, the Brazilian Tax Authority has developed a debatable argument outlined in the solution to Consultation Cosit No. 13. It states that the profits taxed under Brazilian legislation are those earned at the end of each calendar year by the Brazilian investor in proportion to its interest in the investment located abroad and that the profits belong to the Brazilian investor. Due to these controversies, this paper aims to analyze the application of the national tax regime and the rules emanating from the Treaties entered into by Brazil to avoid double taxation of profits earned by foreign subsidiaries whose headquarters are located in countries that have also entered into those Treaties. Based on the available bibliography and the chosen court opinions, the interpretation that Paragraph 1 of Article 7 of the Treaties prevents Brazil from taxing profits earned abroad by subsidiaries of Brazilian companies proved to be legitimate. Therefore, the internal taxation regime, currently established by Article 77 of Law 12.973, of 2014, may not be applied. Whether due to the prevalence of the rules set forth by the Treaties; or due to the lack of a legal basis for the Tax Authority's reasoning for taxing profits under Brazilian law as if those profits had been earned by the investor in Brazil in proportion to its interest in the investment located abroad, the fact is that profits earned abroad by subsidiaries of companies headquartered in countries with which Brazil has entered into Treaties may not be taxed in Brazil unless that profit is actually distributed to the Brazilian company through the appropriate corporate ac